FAKTOR-FAKTOR YANG MEMENGARUHI PEMBELIAN IMPULSIF PELANGGAN DI SUPERMARKET RANCH MARKET [FACTORS AFFECTING CUSTOMERS' IMPULSIVE PURCHASES IN RANCH MARKET SUPERMARKETS] - Jessica Tedja; Margaretha Pink Berlianto (Universitas Pelita Harapan, 2021)
The purpose of this study is to investigate the negative effect of pre-shopping preparation tendency toward impulse buying, the negative effect of positive shopping enjoyment tendency toward positive affect, the positive effect of impulse buying tendency toward urge to purchase, the positive effect of positive affect toward urge to purchase, the negative effect of negative affect toward urge to purchase and the positive effect of urge to purchase toward impulse buying at Ranch Market Jakarta. The population of this research is the customer of Ranch Market Jakarta. The result of this study is pre-shopping preparation tendency has no negative effect toward impulse buying, shopping enjoyment tendency has positive effect toward positive affect, impulse buying tendency has positive effect toward urge to purchase, positive affect has positive effect toward urge to purchase, negative affect has negative effect toward urge to purchase dan urge to purchase has positive effect toward impulse buying.BAHASA INDONESIA ABSTRACTPenelitian ini bertujuan untuk menginvestigasi pengaruh negatif pre-shopping preparation tendency terhadap impulse buying, pengaruh positive shopping enjoyment tendency terhadap positive affect, pengaruh positive impulse buying tendency berpengaruh positive terhadap urge to purchase, pengaruh positive affect terhadap urge to purchase, pengaruh negative affect terhadap urge to purchase dan pengaruh positive urge to purchase terhadap impulse buying di Ranch Market Jakarta. Populasi dari penelitian ini individu yang pernah berbelanja di Ranch Market Jakarta. Hasil penelitian menemukan bahwa pre-shopping preparation tendency tidak berpengaruh negatif terhadap impulse buying, shopping enjoyment tendency berpengaruh positif terhadap positive affect, impulse buying tendency berpengaruh positif terhadap urge purchase, positive affect berpengaruh positif terhadap urge to purchase, negative affect berpengaruh negatif terhadap urge to purchase dan urge to purchase berpengaruh positif terhadap impulse buying.